MEDIAL MALLEOLUS FRACTURE WITH INFERIOR TIBIAL FIBULA LIGAMENT INJURY: CASE REPORT (Proceedings of the International Conference of Community Health and Medical Sciences, 2024)
The medial malleolus and Distal Inferior Tibia Fibula ligaments are part of the structure that supports the stability of the ankle. Medial malleolus fracture with an injury or rupture of the inferior tibial and fibular ligament have not been much discussed at this time. There is still debate about the management of medial malleolus fractures, as well as injuries to the inferior tibial and fibula ligaments. Some opinions tend to carry out surgical intervention for "displaced" medial malleolus fracture with an injury to the inferior tibial fibula ligament rupture because these two organs are supporters of ankle stability and as a nonoperative result that leaves symptoms of Chronic Ankle Instability (CAI). Open reposition internal fixation of medial malleolus fractures and injury or rupture of the inferior tibial and fibula ligaments are options for treatment ankle instability and arthritis. In this case, a 36-year-old man was crushed on his right ankle by a forklift machine. After a physical examination and X-Ray of the ankle, he was diagnosed with a displaced medial malleolus fracture with an injury to the dextra inferior tibia fibula ligament. Open reposition internal fixation were performed on the medial malleolus and distal tibia fibula. Post operation, deformity and alignment was corrected. X-Ray of ankle medial malleolus and distal tibia fibula well positioned.
Keywords: medial malleolus; inferior tibia fibula ligament; fracture; ligament rupture; ORIF